New Approach to Fractal Approximation of Vector-Functions - Konstantin Igudesman; Marsel Davletbaev; Gleb Shabernev (Abstract and Applied Analysis)
This paper introduces new approach to approximation of continuous vector-functions and vector sequences by fractal interpolation vector-functions which are multidimensional generalization of fractal interpolation functions. Best values of fractal interpolation vector-functions parameters are found. We give schemes of approximation of some sets of data and consider examples of approximation of smooth curves with different conditions.